USWAG revitalization of Mandurriao Public Market - Checa, Therese Anne B. (College of Architecture, University of the Philippines Diliman, 2020)
As time pass by, there are more cities emerging in the Philippines. A product of colonization, the Philippines became a culturally rich country and has adapted the ways of its colonizers. The town grew into cities as the local economy thrived along with its development. But with the emergence of cities came the rapid increase in population, thus, a greater demand for necessities for survival. Many amongst those who are affected are people who are not privileged enough to work a formal job due to different factors such as the education and skills. Most of those people work in the market. Some are street hawkers who are looking for opportunities to earn enough for their families. However small they may be, they contribute the most to the economy of the city. However, oftentimes, they are neglected as what can be seen on how they are being treated as decades. Incorporating these public markets into a better environment for social integration will help the maintenance of the place and also help the community as well.